EFFECTS OFTELEREHABILITATION ANDYOUTUBE® PLATFORM-BASED EXERCISE VIDEOS IN PATIENTS WITH AXIAL SPONDILOARTHRITIS: A RANDOMIZED CONTROLLED STUDY - Yentur, S. Baglan; Boyrazli, I. S.; Elbasti, M. S.; Koca, S. S. (Elsevier, 2025)
[Abstract Not Available]
EULAR European Congress of Rheumatology -- JUN 11-14, 2025 -- Barcelona, SPAIN
Keywords: Pain; Randomized controlled trial; Physical therapy; Physiotherapy; and Physical Activity; Clinical Trial